Printed UAV design using fire Resistance Materials & development for an Internet of Public Safety in Smart Cities - Vinothini V R, Sakthisudhan K, Mohanraj S, Archana M (International Journal of Advanced Science and Technology, 2020)
The paper is proposed the vermiculite printed drone and implemented to public safety in the smart cities. The drone act backbone of wireless transmission of instant delivery and disaster recovery managements. It brings the connectivity for discovering areas that challenging to reach and rising surge capacity for public safety. Moreover, it offers the critical facilities like as real time monitoring, decision making and analysis during the disaster period to support public safety and analysis during the disaster period to support public safety and recovery assistant conditions. Hence, the development of drone based wireless transmission can effort in the safety assistant during emerging situation to prevent ecosystem. The development of the proposed research to make the fighting, monitoring, and measuring the safety fields. Since, the drone is printed vermiculite material that able to capable to stand 1000 degree Celsius temperatures. Therefore, these drones implemented for internet of public safety things and that is fulfilment the accuracy and efficiency during emergency instant.